Comparison of Industrial Relations Systems in Developed and Developing Countries (Case Study of Singapore & Indonesia) - Jaya, Jepri; Syahdan Naufal Ghinanda; Hendra Wiguna (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research discusses the comparison of industrial relations systems in Indonesia and Singapore. Indonesia and Singapore basically have differences in country status where Indonesia is a developing country and Singapore is a developed country. The research method used in this research is qualitative using a literature study approach. Industrial relations in Indonesia itself are regulated in the law which regulates industrial or employment issues. There have been several changes to the laws implemented by Indonesia, and Singapore itself has also twice amended the regulations governing industrial relations in its country. With changes to the regulations made by the Indonesian government, up to now there are still quite a lot of problems in industrial relations in Indonesia